BUILDING HALAL FOOD CONSUMER LOYALTY: THE ROLE OF PRODUCT QUALITY, PRICE, AND BRAND IMAGE IN THE E-COMMERCE ECOSYSTEM - Bagas Wicaksono; Muhammad Sholahuddin (MANAJEMEN DEWANTARA, 2026)
This research explores how product quality, pricing, and brand image shape consumer satisfaction in the halal food e-commerce sector, while also investigating the role of consumer loyalty as a connecting mechanism. Through this perspective, the study aims to generate practical insights that help halal food businesses and online platforms strengthen customer satisfaction and build sustainable, long-term loyalty. This study adopted a quantitative explanatory approach, relying on primary data obtained through structured online questionnaires. The survey targeted Muslim consumers in Indonesia aged 18–45 who had purchased halal food via e-commerce services such as GoFood, GrabFood, or ShopeeFood at least twice within the last three months, selected through purposive sampling. Measurement indicators were drawn from prior research and assessed using a five-point Likert scale. The data were processed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0, encompassing outer model testing for validity and reliability, as well as inner model analysis for hypothesis testing through bootstrapping at a 5% significance level.. The results show that product quality, price, and brand image positively and significantly affect customer satisfaction, with product quality emerging as the strongest determinant. However, consumer loyalty does not significantly mediate these relationships, indicating that these factors primarily influence satisfaction directly. The findings suggest that halal food businesses should prioritize high-quality products, fair pricing, and strong brand image to enhance customer satisfaction and support long-term loyaltys.